Screening individual hybridomas by microengraving to discover monoclonal antibodies - Ogunniyi, Adebola O (2009)
The demand for monoclonal antibodies (mAbs) in biomedical research is significant, but the current methodologies used to discover them are both lengthy and costly. Consequently, the diversity of antibodies available for any particular antigen remains limited. Microengraving is a soft lithographic technique that provides a rapid and efficient alternative for discovering new mAbs. This protocol describes how to use microengraving to screen mouse hybridomas to establish new cell lines producing unique mAbs. Single cells from a polyclonal population are isolated into an array of microscale wells (~10(5) cells per screen). The array is then used to print a protein microarray, where each element contains the antibodies captured from individual wells. The antibodies on the microarray are screened with antigens of interest, and mapped to the corresponding cells, which are then recovered from their microwells by micromanipulation. Screening and retrieval require approximately 1–3 d (9–12 d including the steps for preparing arrays of microwells).